2016
DOI: 10.1113/jp273396
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acetylcysteine, a glutathione precursor, reverts vascular dysfunction and endothelial epigenetic programming in intrauterine growth restricted guinea pigs

Abstract: In humans, intrauterine growth restriction (IUGR) is associated with vascular dysfunction, oxidative stress and signs of endothelial programming in umbilical vessels. We aimed to determine the effects of maternal antioxidant treatment with N-acetylcysteine (NAC) on fetal endothelial function and endothelial nitric oxide synthase (eNOS) programming in IUGR guinea pigs. IUGR was induced by implanting ameroid constrictors on uterine arteries of pregnant guinea pigs at mid gestation, half of the sows receiving NAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 56 publications
(132 reference statements)
4
64
0
Order By: Relevance
“…Additionally, an impaired foetal growth in humans is associated with vascular remodelling in the aorta at birth, as well as an increased aortic stiffness at childhood . Recent reports show that growth‐restricted guinea‐pig foetuses have an impaired NOS‐dependent relaxation in systemic and umbilical arteries which occurs in parallel with pro‐constrictive vascular remodelling in the aorta and femoral arteries, but not in the carotid artery . In this study, FGR adult guinea‐pigs showed an increased in vivo femoral vascular resistance with no diurnal variability, but a normal resistance in the carotid artery.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Additionally, an impaired foetal growth in humans is associated with vascular remodelling in the aorta at birth, as well as an increased aortic stiffness at childhood . Recent reports show that growth‐restricted guinea‐pig foetuses have an impaired NOS‐dependent relaxation in systemic and umbilical arteries which occurs in parallel with pro‐constrictive vascular remodelling in the aorta and femoral arteries, but not in the carotid artery . In this study, FGR adult guinea‐pigs showed an increased in vivo femoral vascular resistance with no diurnal variability, but a normal resistance in the carotid artery.…”
Section: Discussionmentioning
confidence: 52%
“…Specifically, altered expression of eNOS in FGR‐derived endothelium results from diverse epigenetic modifications in the NOS3 gene promoter, an effect that can be reprogrammed to a “normal type” by knocking‐down DNMT1 . Additionally, we recently reported that FGR results in an altered eNOS expression and Nos3 gene promoter DNA methylation in a guinea‐pig model of FGR, which is comparable between foetal systemic and umbilical arteries . Notably, maternal antioxidant treatment with N‐acetylcysteine (NAC) restored foetal growth by enhancing placental efficiency and reverting the functional and epigenetic programming of eNOS in arterial endothelium .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently addressed the role of oxidative stress in FGR by treating pregnant guinea pigs with N-acetyl cysteine, a glutathione precursor, during the second half of gestation. Our results show that maternal treatment with NAC restores fetal growth by increasing placental efficiency and reverses endothelial dysfunction in FGR guinea pigs [38]. Similarly, in ovo melatonin administration to chronic hypoxic chick embryos reduces the levels of oxidative stress markers (i.e., lipid peroxidation and protein nitration), by increasing the expression of glutathione peroxidase (GPx), an antioxidant enzyme [28].…”
Section: Hypoxia and Oxidative Stress In Fgrmentioning
confidence: 82%
“…Notably, the altered expression of eNOS was reversed by silencing DNMT1 expression in FGR EC, which restored the DNA methylation pattern at NOS3 promoter, as well as the regulation of eNOS expression induced by hypoxia [12]. Furthermore, using a guinea pig model of FGR, we compared the eNOS expression and DNA methylation pattern at Nos3 promoter to clarify whether these epigenetic changes occurring in umbilical EC would represent changes that take place in systemic arteries (i.e., aorta and femoral) [38]. We found comparable changes in eNOS expression which were associated with specific changes in DNA methylation of Nos3 promoter in the different FGR EC studied, suggesting the presence of a common programming of endothelial dysfunction in the umbilical-placental and systemic circulation.…”
Section: Epigenetics and Endothelial Dysfunctionmentioning
confidence: 99%